APPLICATION OF THINK TALK WRITE MODEL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL ACHIEVEMENT - Soselisa, Novita Jenianis; Gaspersz, Magy; Ngilawajan, Darma Andreas (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2020)
The aim of this research is to know about the improve of the students’ achievement in learning algebra operations by using Think Talk Write (TTW) models on 7th grade students of SMP Kartika XIII-1 Ambon. The subjects of this research are 21 students on 7th grade at SMP Kartika XIII-1 in academic year 2017/2018. The type of this research is Classroom Action Research which taken 2 cycles in order to reach students’ achievement by most students in the class. Data of this research is obtained by using test instrument and observation sheets. Research data is analyzed by using qualitative and quantitative data analysis. After applying Think Talk Write model, the results show that there is improvement in cycle II. In cycle I, there are 6 students who have final test score ≥ 75 (28,57%). In cycle II, there are 18 students who have final test sore ≥75 (85,71%). According to students’ final test scores in cycle I and cycle II, there can be concluded that there is a significant improvement in cycle II, with the value of improvement of cycle I to cycle II as 57,14%